Letter from J. J. Murdock to Arnold O. Beckman - Murdock, J. J. (1935)
Murdock references receipt of correspondence and a blood sample from Noyes, expresses pleasure at Millikan's interest in his work, and discusses real estate matters, including the erection of apartment buildings.
Keywords: Millikan, Robert Andrews, 1868-1953; Noyes, Arthur A. (Arthur Amos), 1866-1936; Real estate development; Beckman Instruments, Inc.